Proceedings of Sixth International Congress on Information and Communication Technology ICICT 2021, London, Volume 4 - Yang, Xin-She; Sherratt, Simon; Dey, Nilanjan; Joshi, Amit (Lecture Notes in Networks and Systems, 2022)
XXVIII, 898 p. 360 illus., 269 illus. in color.